PERENCANAANKARIRPEGAWAIDISEKRETARIATDAERAH KABUPATENMERAUKE - Hesty Tambajong (SOCIETAS, 2015)
ABSTRACT Officials career planning is the process by which one to choose career goals and career lanes in the organization sector in institutions. The aims of the research were to find out career planning system in Regional Secretariat of Merauke Regency and identify factors - factors that affect the process of career planning in Regional Secretariat of Merauke Regency. The research used quantitative method supported by qualitative data or mixed-methods-approach. The methods of obtaining the data were questionnaire, direct observation, interviews, and documentation study. The samples were determined using disproportionate stratified random sampling method. The data were analyzed descriptively based on frequency calculation on the score vulnerable scala. The results of the research indicate that career planning of formal education indicator is in a good category to support career planning, the result of for work experience indicator is quite good, but it is not optimum for officials’ career planning and development, superior’s attitude indicator is less able to support official’s career planning, work achievement indicator is assessed objectively, and it runs well, work load indicator is quite good to support career planning, job vacancy indicator runs quite good, while work productivity indicator runs well. The factors affecting career planning are the level of career life and career basic, i.e. managerial ability, technical ability possessed by the officials can also make them get a higher position since it is influenced by the proximity with the leader, security of a career level of a leader still considered to rely on good relations with policy makers. creativity in a local bureaucracy has a narrow space since is limited by rules and main duties and functions by officials. The only freedom given is responsibility freedom, and it does not deviate from the tasks given by the agency.